Analysis of Marketing Mix on Property Purchase Decision in Harvest City - Fatwara, Medy Desma; Sundara, Dadan (Indonesian Journal Economic Review (IJER), 2025)
Promotion and Location. The data used in this research are primary data with the Purposive Sampling method. Purposive sampling is conducted by intentionally distributing questionnaires to consumers who have purchased property in Harvest City, totaling 50 respondents. The data were analyzed using Smart PLS software. The analysis technique used in this study is multiple linear regression. The results show that partially, the variables of Product (X1), Price (X2), Place (X3), and Promotion (X4) significantly affect the Purchase Decision (Y). Meanwhile, simultaneously, the variables of Product (X1), Price (X2), Place (X3), and Promotion (X4) also significantly influence the Purchase Decision (Y).